2016
DOI: 10.14710/ijred.5.1.33-42
|View full text |Cite
|
Sign up to set email alerts
|

Design, Analysis and Optimization of a Solar Dish/Stirling System

Abstract: In this paper, a mathematical model by which the thermal and physical behavior of a solar dish/Stirling system was investigated, then the system was designed, analysed and optimized. In this regard, all of heat losses in a dish/Stirling system were calculated, then, the output net-work of the Stirling engine was computed, and accordingly, the system efficiency was worked out. These heat losses include convection and conduction heat losses, radiation heat losses by emission in the cavity receiver, reflection he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 17 publications
(22 reference statements)
0
12
0
1
Order By: Relevance
“…The heat energy transferred to the Stirling engine depends upon the efficiencies of the concentrator and the receiver, the DNI value and the thermal losses, as described by Equations () and () 47,48 . Higher the temperature difference, more will be the thermal losses. Qeng=QcQref()Qcon+Qconv+Qrad, Qeng=ƞr·ƞc·italicDNI·Ac, …”
Section: Design Development and Performance Evaluation Of Csp‐dssmentioning
confidence: 99%
See 2 more Smart Citations
“…The heat energy transferred to the Stirling engine depends upon the efficiencies of the concentrator and the receiver, the DNI value and the thermal losses, as described by Equations () and () 47,48 . Higher the temperature difference, more will be the thermal losses. Qeng=QcQref()Qcon+Qconv+Qrad, Qeng=ƞr·ƞc·italicDNI·Ac, …”
Section: Design Development and Performance Evaluation Of Csp‐dssmentioning
confidence: 99%
“…The total receiver thermal losses ( Q total,loss ) including the conduction loss ( Q cond ), the convection loss ( Q conv ), and the radiation loss ( Q rad ) are described by Equations () 47,48 . The influencing parameters included are cavity temperature ( T cav ), ambient temperature ( T amb ), cavity diameter ( D cav ), cavity length ( L cav ), and thickness of insulator ( δ ins ), heat transfer coefficient ( h T ), and emissivity of material ( ℰ ). Qtotal,loss=Qcond+Qconv+Qrad+Qrad, Qcond=TcavTambitalicLn[]Dcav2+δinsDcav2/()2π·Kins·Lcav, Qconv=hT·Acav0.25em()TabsTamb, Qrad=rad·σ·Aap0.25em()T4absT4amb· …”
Section: Design Development and Performance Evaluation Of Csp‐dssmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the main idea is to find the optimal combination of prismatic crystals to enhance sunlight energy transmission via optic fiber. Nazemi and Boroushaki describe the optimal design of a dish/stirling system in [15]. The model considers the parabolic dish and the cavity receiver as the optimization problem, and the metaheuristic used was particle swarm optimization.…”
Section: Introductionmentioning
confidence: 99%
“…According to their numerical results, it was observed that acetamide and stearic acid should be used as thermal storage in boxtype solar cooker. Najemi & Boroushaki (2016) calculated heat losses in solar dish/Stirling system using mathematical modeling and simulation. Their simulation results were compared with experimental data of Eurodish system and showed a reasonable heat loss in Stirling engine and cavity receiver.…”
Section: Introductionmentioning
confidence: 99%